Learning English with Technology: A Study - Andi Febriana Tamrin; Basri Basri (UICELL, 2019)
The growth and development of information and technology has greatly improve for learning language, especially English. The aim of this study is to explored the potentials and the challenges of implementing technologies for learning English. Qualitative descriptive design was applied. Observation and interview were implemented to collect the data. This study was conducted at Universitas Fajar, Architecture Department. There were ten students were involved in this research. They were selected based on the purposive sampling. The result of this study depicted that applying technologies (e-learning and online application) have two main potentials and one challenges in regards for the implementation of technologies in learning English.